Clinical Pulp Fiction - Claire F. Woodworth, MD; Susan M. Fagan, MD; Scott R. Harris, MD; Corey Adams, MD (JACC: Case Reports, 2020)
A 21-year-old woman self-ingested an 18-gauge needle that perforated the distal esophagus into the left inferior ventricular myocardium, with migration into the septum. Radiography, computed tomography, and echocardiography imaging characterized the needle’s location. Following an initial endoscopy and pericardial tamponade drainage, complete needle removal occurred via median sternotomy and cardiopulmonary bypass. (Level of Difficulty: Intermediate.)